Linguocognitive descriptors of artist’s artistic creativity in the novel by P. Zagrebelnyj “Dyvo” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article dwells upon linguocognitive descriptors regarding to the interpretation of the artist’s artistic creativity in the novel by P. Zagrebelnyi’s “Dyvo”. The author interprets the artistic panorama created by the artist as balance that involves a moving correlation of colours of the spectrum / dual background (religious-thematic and external – the image of the solstice by reincarnating the pictures of the real world with the help of the corresponding sign material – colour, space, and light). The groups of linguistic means of reproduction of the light-to-dark contrast of the artistic manner of the master are distinguished: 1) the contrast of colours, revealing in the text fragment the character of repetitions or alternations of parts of the whole, creating the effect of the rhythm (tonal, colour, linear, spatial, textured expressions in the painting of frescoes); 2) the reproduction of the artistic image on the basis of the law of symmetry: the correct arrangement of parts of the whole centrifugal. The relationship of symmetry – the rhythm is universal, which allows the writer to reproduce through the colours the internal sense of harmony and disharmony; 3) the expressiveness of the artist’s painting is achieved through the organization of the target colour vector, which is in equilibrium, combine, and acquire consistency and order. The compositional equilibrium (balance) of artistic images consists of the equilibrium of the main and additional centers – the dominant, the balance between the “spots” (part of the composition) – and the equilibrium of the optical movements of the forms in the right and left parts of the composition.At the level of sensory codes, the criterion of quantity, incorporated into the composition of murals and mosaics, becomes significant. This allows us to speak about the dimension of a cultural form oriented on the development of ideological knowledge, value orientations and ideals. The artistic path from the point of view of artistic reflection is considered at the level of correlation: painting (craft) – art; painter – artist; artwork / life script; life experience / cultural form (fresco, mosaic). The artist's realization is understood as the achievement of harmony in the reproduced reality, and the work of art is generated from the beginning of the individual units, the sacred interconnection that the artist finds through the hard work and the sense of consistency of the components (harmony: sources and origins / squeal (dissonance) of things / thing of the world). The concept of beauty, harmony has the basis not only of the established canons, but also the ideological and religious basis, the sensory component – the ability to feel the master of their content at the level of the inner world – the soul.
Keywords: linguocultural approach; linguocognitive descriptor; language categorization; artistic reflection; artistic image; aesthetics of artistic work